Luz, câmera, animação : uma reflexão sobre a construção dos conceitos de geometria espacial - Dall' Acua, Graziele (My University, 2018)
In this work, it is presented a research in Science and Mathematics Teaching, which consisted in the investigation of a pedagogical practice applied to students of the 8th year of Elementary School, about the concepts of Spatial Geometry. In view of the discrepancy between the curricular grid of the Municipality, in which the students are inserted and the new National Common Curricular Base, as well as, the curiosity and the desire to do more of the researcher, the theme of this research appeared. Conceived to understand how the production of audiovisuals with the aid of manipulable materials can contribute to the appropriation of the concepts of Spatial Geometry, the project achieved its main objective that was to promote the occurrence of learning of Spatial Geometry concepts through the use of manipulable materials and the production of audiovisuals. Based on Paulo Freire’s theoretical conceptions of learning, which has autonomy as an educational principle, this project also developed solid foundations for a new educommunicational model, essentially horizontal, democratic and dialogic of the Educommunication. It was promoted the construction of communicative ecosystems, developing a dynamic and pleasant process structured through the Three Pedagogical Moments. A mediative evaluation was at the service of the students' learning and of the improvement of the pedagogical action, contemplating the self-assessment of both the students and the teacher. The data, built and tabulated through Discursive Textual Analysis, showed the progress of the students in the development of the five geometric, for the learning of Geometry to occur: Visual, Verbal, Graphic, Logic and Application abilities. In addition, autonomy was fostered that generated ideal conditions for the development of knowledge, freedom of expression, creativity, and dialogue, and what Freire calls "Think Right". As a final product, a didactic guide was developed, that can be used as learning resources by other Basic Education teachers.
Neste trabalho, apresenta-se uma pesquisa em Ensino de Ciências e Matemática que consistiu na investigação de uma prática pedagógica aplicada a estudantes do 8º ano do Ensino Fundamental, sobre conceitos de Geometria Espacial. A temática desenvolvida surgiu diante da discrepância observada entre os conteúdos da grade curricular do município no qual os estudantes estavam inseridos e aqueles indicados na Base Nacional Comum Curricular (em versão preliminar disponível à época do início da pesquisa), aliada à curiosidade e à vontade de aprimorar a prática pedagógica da professora pesquisadora. Concebido para compreender qual a contribuição de uma proposta didática que integra a utilização de materiais manipuláveis e a produção de audiovisuais na apropriação de conceitos, o projeto atingiu seu objetivo principal: o de promover a aprendizagem de conteúdos de Geometria Espacial. Embasado nas concepções teóricas de Paulo Freire sobre a aprendizagem, que têm a autonomia como princípio educativo, este projeto também desenvolveu fundamentos sólidos para um novo modelo educomunicacional, democrático e dialógico da Educomunicação. Promoveu-se, outrossim, a construção de ecossistemas comunicativos, desenvolvendo um processo dinâmico e prazeroso, estruturado através dos Três Momentos Pedagógicos. Uma avaliação mediadora esteve a serviço da aprendizagem e da melhoria da ação pedagógica, contemplando a autoavaliação, tanto por parte dos estudantes, quanto da professora. Os dados, obtidos e analisados seguindo orientações da análise textual discursiva, mostraram o progresso dos estudantes no desenvolvimento de cinco habilidades geométricas: a visual, a verbal, a gráfica, a lógica e a de aplicação. Além disso, ao se promover a autonomia, geraram-se condições para a construção de conhecimentos, liberdade de expressão, criatividade, dialogicidade e o que Freire chama de “pensar certo”. Como produto final, foi elaborado um guia didático, que pode servir como recurso de aprendizagem a ser utilizado por outros professores de Educação Básica.
Keywords: Geometria espacial - Estudo e ensino; Geometria espacial; Aprendizagem ativa; Geometry, Solid - Study and teaching; Geometry, Solid; Active learning